Properties of activated blended cement containing high content of calcined clay - Marangu, Joseph M.; Karanja, Thiong’o J.; Wachira, Jackson M. (Elsevier, 2018)
This paper presents findings of an experimental investigation on sodium sulphate (Na2SO4) activated calcined clay e Portland cement blends in sulphuric acid media. Calcined clays were blended with Ordinary Portland Cement (OPC) at replacement levels of 40% 45% and 50 % by mass of OPC to make blended cement labelled PCC40, PCC45 and PCC50 respectively. Initially, pozzolanicity and setting time tests were conducted. Mortar prisms measuring 40 mm 40 mm 160 mm were cast using 0.5M Na2SO4 solution and their compressive strengths determined on the 2nd, 7th, 28th and 90 th day of curing. The 28th day cured mortar prisms were subjected to porosity test. Moreover, 5 5 5 cm mortar cubes were also prepared and their weight and strength loss was taken as a measure of their acid resistivity after an immersion time of 7, 14, 28, 56, 84 and 120 days in 3 % of sulphuric acid at 23 1 C. OPC, commercial Portland Pozzolana Cement (PPC) and PCC40, PCC45 and PCC50 cement were cast using water and similarly investigated for comparison purposes. The results obtained showed that chemically activated cements exhibited higher pozzolanic activity, lower porosity, shorter setting times and higher resistance to acid attack compared to non-activated cements. However, OPC was found to be non-pozzolanic.
Keywords: Civil engineering; Industrial engineering; Materials science